Extracorporeal Membrane Oxygenation Candidacy in Pediatric Patients Treated With Hematopoietic Stem Cell Transplant and Chimeric Antigen Receptor T-Cell Therapy: An International Survey - Ghafoor, Saad; Fan, Kimberly; Di Nardo, Matteo; Talleur, Aimee C.; Saini, Arun; Potera, Renee M.; Lehmann, Leslie; Annich, Gail; Wang, Fang; McArthur, Jennifer; Sandhu, Hitesh (Frontiers in Oncology, 2021)
Introduction: Pediatric patients who undergo hematopoietic cell transplant (HCT) or chimeric antigen receptor T-cell (CAR-T) therapy are at high risk for complications leading to organ failure and the need for critical care resources. Extracorporeal membrane oxygenation (ECMO) is a supportive modality that is used for cardiac and respiratory failure refractory to conventional therapies. While the use of ECMO is increasing for patients who receive HCT, candidacy for these patients remains controversial. We therefore surveyed pediatric critical care and HCT providers across North America and Europe to evaluate current provider opinions and decision-making and institutional practices regarding ECMO use for patients treated with HCT or CAR-T. Methods: An electronic twenty-eight question survey was distributed to pediatric critical care and HCT providers practicing in North America (United States and Canada) and Europe through the Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) Network and individual emails. Responses to the survey were recorded in a REDCap database. Results: Two-hundred and ten participants completed the survey. Of these, 159 (76%) identified themselves as pediatric critical care physicians and 47 (22%) as pediatric HCT physicians or oncologists. The majority (99.5%) of survey respondents stated that they would consider patients treated with HCT or CAR-T therapy as candidates for ECMO support. However, pediatric critical care physicians identified more absolute and relative contraindications for ECMO than non-pediatric critical care physicians. While only 0.5% of respondents reported that they consider HCT as an absolute contraindication for ECMO, 6% of respondents stated that ECMO is contraindicated in HCT patients within their institution and only 23% have an institutional protocol or policy to guide the evaluation for ECMO candidacy of these patients. Almost half (49.1%) of respondents would accept a survival to hospital discharge of 20-30% for pediatric HCT patients requiring ECMO as adequate. Conclusion: ECMO use for pediatric patients treated with HCT and CAR-T therapy is generally acceptable amongst physicians. However, there are differences in the evaluation and decision-making regarding ECMO candidacy amongst providers across medical specialties and institutions. Therefore, multidisciplinary collaboration is an essential component in establishing practice guidelines and advancing ECMO outcomes for these patients.